FAKTOR-FAKTOR YANG MEMPENGARUHI CUSTOMER SWITCHING DARI TAKSI KONVENSIONAL KE TAKSI ONLINE - Juniawan, Jefri Eko; Artha Kusuma, Anak Agung Gede Agung (E-Jurnal Manajemen; Vol 6 No 10 (2017), 2017)
Sharing Economy is business concept that offering cooperation with to societies to utilize a resources that we have, the concept. Have done by online taxi like as Grabcar, Uber, and Gocar.It’s motivate to customer switching from convensional taxi toonline taxi. This business concept must be exploit not be a problem. This research have a goals to know what’s are the factor that influence the customer switching from conventional taxi to online taxi. Adding totaling of sample that used are 182 respondents with technology non probability sampling usage, expexially purposive sampling. Collected and processed data use Confirmatory Factor Analysis (CFA) technology. The result researching find and factor customer switching shaper that researched and reduced because five factors that make a customer switching from conventional taxi to online taxi, are Pricing, Core service failure, Service encounters failure, Employee responses to service failure, andEthical Problems.